Step 1: Determine the conjugate of the denominator. ( to find the conjugate just change the sign of the imaginary part ).
In this example, the conjugate of $ \color{orangered}{ 2+3i }\, $ is $ \color{blue}{ 2-3i } $.
Step 2: Multiply both the numerator and denominator by the conjugate:
$$\begin{aligned} \frac{ 3+2i }{ 2+3i } &= \frac{ 3+2i }{ 2+3i } \cdot \frac{ \color{blue}{ 2-3i } }{ \color{blue}{ 2-3i } } = \\[1 em] &= \frac{ \left( 3+2i \right) \cdot \left( 2-3i \right) }{ \left( 2+3i \right) \cdot \left( 2-3i \right) } \end{aligned} $$Step 3: Simplify numerator and denominator (use $\color{blue}{i^2 = -1}$)
$$ \begin{aligned} \left( 3+2i \right) \cdot \left( 2-3i \right) &= 3 \cdot 2 + 3 \cdot \left(-3 \,i \right) + \left( 2 \,i \right) \cdot \left(2 \right) + \left( 2 \,i \right) \cdot \left(-3 \,i \right) = \\[1 em] &= 6 -9 \, i + 4 \, i -6 \color{blue}{(-1)} = \\[1 em] &= 12-5i\end{aligned} $$ $$ \begin{aligned} \left( 2+3i \right) \cdot \left( 2-3i \right) &= 2 \cdot 2 + 2 \cdot \left(-3 \,i \right) + \left( 3 \,i \right) \cdot \left(2 \right) + \left( 3 \,i \right) \cdot \left(-3 \,i \right) = \\[1 em] &= 4 -6 \, i + 6 \, i -9 \color{blue}{(-1)} = \\[1 em] &= 13\end{aligned} $$Step 4: Separate real and imaginary parts:
$$ \frac{ 3+2i }{ 2+3i } = \frac{ 12-5i }{ 13 } = \frac{ 12 }{ 13 } + \frac{ -5 }{ 13 } i= \frac{ 12 }{ 13 }-\frac{ 5 }{ 13 }i $$